The Influence Of The Dimensions Of Justice, And The Level Of Awareness Of Taxpayer Compliance With Religiosity As Moderation - Ros Santri Qur'ani; Aisyah Amalina (Yayasan Az Zukhruf Cendikia, 2024)
Purpose - This study aims to obtain empirical evidance about the effect of the Justice Dimension, and Level of Tax Awarennes on Taxpayer Compliance with Religiosity as a moderating variable . Design/methodology/approach - The research uses quantitative research. This research was conducted using a questionnaire distrubuted to people who are employees, people who have worked, and people who have income, namely 150 questionanaires distributed via social media. Each questionnaire distruted 24 statement to be answered by respondents. From the distribution of questionnaires conducted, 50 respondents were obtained whot gave answer. To get the result of this study, researchers used PLS SEM Version 3.0 Findings - The results of this study found that the Justice Dimension has a positive and insignificant effect on Taxpayer Compliance, the Tax Awarennes Level has a positive and insignificant effect on Taxpayers Compliance, Religiosity cannot strenghther the relationship of the justice Dimension to Taxpayers compliance, and Religiosity strengthens the relationship of Tax Awreness level to Taxpayer Compliance Research limitations/implications - this study conntributes to the literature by focusing on the dimensions of justice, level of Tax awareness, and religiosiy needed for tax compliance to support the tax general directorate in the tax compliance movement.